Management of Sheetapitta through Shamana Chikitsa – A Case Study - Ranjeetha , K; Chaitra, H (International Research Journal of Ayurveda & Yoga, 2022)
Background: Urticaria is a red, itchy rash caused by vasodilation, increased blood flow, and increased vascular permeability. The function of infection as a potential trigger for urticaria is unknown, as is the precise mechanism by which infection induces histamine release from mast cells. In Ayurveda this condition has a close resemblance to sheetapitta. Due to the exposure to cold the vitiated kapha and vata dosha gets aggravated combines with pitta dosha. They circulate throughout the shrotas and vitiate the rakthadi dhatus and produces mandalopatti on the surface of skin. Main observations: A 39-year-old female patient, presented with complaints of raised reddish circular lesions all over the body for 5 years associated with itching, also complaints of orbital swelling the diagnosis was done as sheetapitta. Result: The efficacy of Ayurvedic treatment for Urticaria is demonstrated in this case study. Conclusions: The study concluded that ayurvedic medication was significantly effective in treating urticaria.